Persepsi Ekologis Dan Ses Masyarakat Terhadap Penambangan Batu Alam Di Desa Mekarjaya Kecamatan Cigudeg Kabupaten Bogor Provinsi Jawa Barat - Rasminto (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2022)
This study aims to analyze two things, namely: First, how is the sosial, economic and ecological perspective of the surrounding community towards natural stone mining activities; and Second, what factors influence the sosial, economic and ecological perspectives of surrounding communities on natural stone mining activities. This survey research was conducted in Mekarjaya Village, Cigudeg District, Bogor Regency, West Java Province with a population of 1,650 households. Samples totaling 67 respondents were taken randomly using the formula V = p (100-p) Data collection techniques were done through a questionnaire and data analysis was performed using SPSS software Data analysis includes validity testing with the corrected item-total correlation technique, reliability test, Independent T test and structural equation modeling (SEM). The results showed that although the general perception of the surrounding community on natural stone mining activities in Mekarjaya Village was quite good, partially it showed that sosial and ecological perceptions were classified as bad whereas for the economic perception the community was quite good.